Neuropathological evidence of body-first vs. brain-first Lewy body disease - Per Borghammer; Jacob Horsager; Katrine Andersen; Nathalie Van Den Berge; Anna Raunio; Shigeo Murayama; Laura Parkkinen; Liisa Myllykangas (Neurobiology of Disease, 2021)
Aggregation of alpha-synuclein into inclusion bodies, termed Lewy pathology, is a defining feature of Parkinson's disease (PD) and Dementia with Lewy bodies (DLB). In the majority of post mortem cases, the distribution of Lewy pathology seems to follow two overarching patterns: a caudo-rostral pattern with relatively more pathology in the brainstem than in the telencephalon, and an amygdala-centered pattern with the most abundant pathology in the “center of the brain”, including the amygdala, entorhinal cortex, and substantia nigra, and relatively less pathology in the lower brainstem and spinal autonomic nuclei. The recent body-first versus brain-first model of Lewy Body Disorders proposes that the initial pathogenic alpha-synuclein in some patients originates in the enteric nervous system with secondary spreading to the brain; and in other patients originates inside the CNS with secondary spreading to the lower brainstem and peripheral autonomic nervous system. Here, we use two existing post mortem datasets to explore the possibility that clinical body-first and brain-first subtypes are equivalent to the caudo-rostral and amygdala-centered patterns of Lewy pathology seen at post mortem.